2022
DOI: 10.3389/phrs.2022.1604499
|View full text |Cite
|
Sign up to set email alerts
|

Evidence From the Decade of Action for Road Safety: A Systematic Review of the Effectiveness of Interventions in Low and Middle-Income Countries

Abstract: Objectives: To evaluate the effectiveness of road safety interventions in low and middle-income countries (LMICs), considering the principles of systems theory presented in the Global Plan for the Decade of Action for Road Safety.Methods: We conducted a systematic review according to PRISMA guidelines. We searched for original research studies published during 2011–2019 in the following databases: Medline, Embase, PsycInfo, Scopus, Web of Science, Cochrane library, Global Health Library, ProQuest and TRID. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
7
1
Order By: Relevance
“…Generally, amendments to traffic laws are made to reduce traffic injuries [7]. However, this study found no statistically significant difference in the injury severity of the two groups before and after the law revision.…”
Section: Discussioncontrasting
confidence: 71%
“…Generally, amendments to traffic laws are made to reduce traffic injuries [7]. However, this study found no statistically significant difference in the injury severity of the two groups before and after the law revision.…”
Section: Discussioncontrasting
confidence: 71%
“…", as remarked by a recent study of 2015 conceptually analyzing different everyday problems of the country, in which traffic crashes did not even constitute a relevant matter to consider for most Dominicans [56]. In addition, other studies have suggested that this slight perceptual relevance of road safety matters could be strongly influenced by the lack of importance given to safety matters in different scenarios (e.g., mass media, social networks, and policymaking) [57].…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence from systematic reviews and meta-analyses indicates that legislation and enforcement interventions have demonstrated significant impact, particularly in Low-and Middle-Income Countries (LMICs) (11). These findings suggest that implementing and enforcing road safety laws, including enforcing speed limits and a helmet wearing law in LMICs can lead to significant improvements in road safety outcomes.…”
Section: Benefits Of Reducing Speed Limits and Stronger Enforcementmentioning
confidence: 99%
“…One of the most effective ways to reduce speeding behaviour and increase helmet wearing rates is through stronger enforcement (11,12). Studies have shown that riders indicated that the fear of being caught was the most significant factor influencing decision-making regarding driving speed and travelling within the speed limit (13).…”
Section: Introductionmentioning
confidence: 99%